Scalable Antifouling Reverse Osmosis Membranes Utilizing Perfluorophenyl Azide Photochemistry. Issue 17 (8th July 2014) - McVerry, Brian T.; Wong, Mavis C. Y.; Marsh, Kristofer L.; Temple, James A. T.; Marambio‐Jones, Catalina; Hoek, Eric M. V.; Kaner, Richard B.
<x xml:space="preserve">Abstract</x> We present a method to produce anti‐fouling reverse osmosis (RO) membranes that maintains the process and scalability of current RO membrane manufacturing. Utilizing perfluorophenyl azide (PFPA) photochemistry, commercial reverse osmosis membranes were dipped into an aqueous solution containing PFPA‐terminated poly(ethyleneglycol) species and then exposed to ultraviolet light under ambient conditions, a process that can easily be adapted to a roll‐to‐roll process. Successful covalent modification of commercial reverse osmosis membranes was confirmed with attenuated total reflectance infrared spectroscopy and contact angle measurements. By employing X‐ray photoelectron spectroscopy, it was determined that PFPAs undergo UV‐generated nitrene addition and bind to the membrane through an aziridine linkage. After modification with the PFPA‐PEG derivatives, the reverse osmosis membranes exhibit high fouling‐resistance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>